2020
DOI: 10.3389/fgene.2020.00546
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genetic and Allelic Diversity Amongst Cultivated and Wild Lentil Accessions for Germplasm Enhancement

Abstract: Intensive breeding of cultivated lentil has resulted in a relatively narrow genetic base, which limits the options to increase crop productivity through selection. Assessment of genetic diversity in the wild gene pool of lentil, as well as characterization of useful and novel alleles/genes that can be introgressed into elite germplasm, presents new opportunities and pathways for germplasm enhancement, followed by successful crop improvement. In the current study, a lentil collection consisting of 467 wild and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 54 publications
(75 reference statements)
5
29
3
Order By: Relevance
“…For questions pertaining to population structure and phylogenetic relationships, filtering conditions did not affect the results. Population structure analyses and phylogenies inferred were similar to previous studies: four or five groups, when different species within Lens are considered (depending on whether orientalis and culinaris are split or not) (Alo et al, 2011;Ogutcen et al, 2018;Dissanayake et al, 2020); and three major clusters within cultivated lentils (Khazaei et al, 2016;Koul et al, 2017).…”
Section: Methodsological Issuessupporting
confidence: 77%
See 1 more Smart Citation
“…For questions pertaining to population structure and phylogenetic relationships, filtering conditions did not affect the results. Population structure analyses and phylogenies inferred were similar to previous studies: four or five groups, when different species within Lens are considered (depending on whether orientalis and culinaris are split or not) (Alo et al, 2011;Ogutcen et al, 2018;Dissanayake et al, 2020); and three major clusters within cultivated lentils (Khazaei et al, 2016;Koul et al, 2017).…”
Section: Methodsological Issuessupporting
confidence: 77%
“…Misclassification of samples is a recurrent issue with germplasm accessions (Mason et al, 2015). In lentil studies, Dissanayake et al (2020) observed 22 misclassified accessions out of 467 lentil accessions, and 4 out of 83 accessions were identified as erroneously classified by Wong et al (2015). Less straightforward is how to deal with accessions that are putative hybrids between different groups or that could have been affected by gene flow along their evolutionary past.…”
Section: Methodsological Issuesmentioning
confidence: 99%
“…The VCF file was then filtered for a minimum read depth (DP) of 5, maximum missing data of 80%, base quality of 30 (Q30), minimum minor allelic frequency (MAF) of 5%, and heterozygosity of 20%, using VCFtools (version 0.1.16) [48] and the TASSEL software package (Trait Analysis by aSSociation, Evolution, and Linkage; version 5.2.48) [49]. Genetic diversity of the studied lentil population was also analyzed based on the method described in Dissanayake et al [38] using the StAMPP package [50] and DARwin-6.0.17 software [51] ( Figure S1).…”
Section: Tgbs Library Preparation Sequencing and Variant Callingmentioning
confidence: 99%
“…Total RNA extraction, library preparation and quality trimming for GBS-t were performed using the method described in Dissanayake et al [38]. The remaining high-quality trimmed sequence reads were aligned to the lentil reference genome sequence of cultivar CDC Redberry (v2.0) [39] using Spliced Transcripts Alignment to a Reference (STAR) aligner (version 2.5.4a) [52].…”
Section: Transcriptome-based Gbs Library Preparation Sequencing Andmentioning
confidence: 99%
See 1 more Smart Citation